SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMA SANTO YOSEPH MEDAN - Sarah Silaen; Roni Jhonson Simamora; Mendarissan Aritonang (Universitas Methodist Indonesia, 2020)
The library is very important in supporting the knowledge and information of students in school because the library is part of the learning resources that must be owned by the school; hence the library is often referred to as the heart of education. At present, the Santo Yoseph Medan High School Library, which is currently processing its library, has not been computerized, making it difficult to process loan transactions and return books, and register as a member and award fines. For this reason, SMA Santo Yoseph Medan requires a library that has a web-based library system. The tool used to design this library information system is to use the PHP and MySql programming languages. The results of this web-based library information system design are expected to help library administrators in the process of borrowing and returning books, processing book data and members, and making library data reports.